Calculating the Resolving Power For Symmetrical Double Pole Piece Magnetic Lenses By Using A Preassigned Analytical Functions - Yaseen, M.J.; Hasan, H.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this theoretical paper  and depending on the optimization synthesis method for electron magnetic lenses a theoretical  computational investigation was carried out to calculate the Resolving Power for the symmetrical double pole piece magnetic lenses,  under the absence of magnetic saturation, operated by the mode of telescopic operation by using symmetrical magnetic field for some analytical functions well-known in electron optics such as Glaserâ€™s Bell-shaped model,  Grivet-Lenz model, Gaussian field model  and Hyperbolic tangent field model.       This work can be extended further by using the same or other models for asymmetrical or symmetrical axial magnetic field under magnetic saturation  or absence of magnetic saturation, operated by other modes operation.